Epinephrine before defibrillation in patients with shockable in-hospital cardiac arrest: propensity matched analysis. (10th November 2021) - Evans, Erin; Swanson, Morgan B; Mohr, Nicholas; Boulos, Nassar; Vaughan-Sarrazin, Mary; Chan, Paul S; Girotra, Saket
Abstract: Objective: To determine the use of epinephrine (adrenaline) before defibrillation for treatment of in-hospital cardiac arrest due to a ventricular arrhythmia and examine its association with patient survival. Design: Propensity matched analysis. Setting: 2000-18 data from 497 hospitals participating in the American Heart Association's Get With The Guidelines-Resuscitation registry. Participants: Adults aged 18 and older with an index in-hospital cardiac arrest due to an initial shockable rhythm treated with defibrillation. Interventions: Administration of epinephrine before first defibrillation. Main outcome measures: Survival to discharge; favorable neurological survival, defined as survival to discharge with none, mild, or moderate neurological disability measured using cerebral performance category scores; and survival after acute resuscitation (that is, return of spontaneous circulation for >20 minutes). A time dependent, propensity matched analysis was performed to adjust for confounding due to indication and evaluate the independent association of epinephrine before defibrillation with study outcomes. Results: Among 34 820 patients with an initial shockable rhythm, 9630 (27.6%) were treated with epinephrine before defibrillation, contrary to current guidelines. In comparison with participants treated with defibrillation first, participants receiving epinephrine first were less likely to have a history of myocardial infarction or heart failure, but more likely to have renal failure, sepsis, pneumonia, and receive mechanical ventilation before in-hospital cardiac arrest (P<0.0001 for all). Treatment with epinephrine before defibrillation was strongly associated with delayed defibrillation (median 3 minutes v 0 minutes). In propensity matched analysis (9011 matched pairs), epinephrine before defibrillation was associated with lower odds of survival to discharge (25.2% v 29.9%; adjusted odds ratio 0.81, 95% confidence interval 0.74 to 0.88; P<0.001), favorable neurological survival (18.6% v 21.4%; 0.85, 0.76 to 0.92; P<0.001), and survival after acute resuscitation (64.4% v 69.4%; 0.76, 0.70 to 0.83; P<0.001). The above findings were consistent in a range of sensitivity analyses, including matching according to defibrillation time. Conclusions: Contrary to current guidelines that prioritize immediate defibrillation for in-hospital cardiac arrest due to a shockable rhythm, more than one in four patients are treated with epinephrine before defibrillation, which is associated with worse survival.